Soluble Interleukin-6 Receptor Regulates Interleukin-6-Dependent Vascular Remodeling in Long-Distance Runners - Villar-Fincheira, Paulina; Paredes, Aaron J.; Hernández-Díaz, Tomás; Norambuena-Soto, Ignacio; Cancino-Arenas, Nicole; Sanhueza-Olivares, Fernanda; Contreras-Briceño, Felipe; Mandiola, Jorge; Bruneau, Nicole; García, Lorena; Ocaranza, María Paz; Troncoso, Rodrigo; et al. (Frontiers in Physiology, 2021)
Little is known about the effects of training load on exercise-induced plasma increase of interleukin-6 (IL-6) and soluble IL-6 receptor (sIL-6R) and their relationship with vascular remodeling. We sought to evaluate the role of sIL 6R as a regulator of IL-6-induced vascular remodeling. Forty-four male marathon runners were recruited and allocated into two groups: low-training (LT, <100 km/week) and high-training (HT, ≥100 km/week), 22 athletes per group. Twenty-one sedentary participants were used as controls. IL-6 and sIL 6R levels were measured in plasma samples obtained before and immediately after finishing a marathon (42.2-km). Aortic diameter was measured by echocardiography. The inhibitory effect of sIL-6R on IL-6-induced VSMC migration was assessed using cultured A7r5 VSMCs. Basal plasma IL-6 and sIL-6R levels were similar among sedentary and athlete groups. Plasma IL-6, sIL-6R and sgp130 levels were elevated after the marathon, and HT athletes had higher post-race plasma sIL-6R, but not IL-6, level than LT athletes. No changes in sgp130 plasma levels were found in LT and HT groups before and after running the marathon. Athletes had a more dilated ascending aorta and aortic root than sedentary participants with no differences between HT and LT athletes. However, a positive correlation between ascending aorta diameter and plasma IL-6 levels corrected by training load and years of training was observed. IL-6 could be responsible for aorta dilation because IL-6 stimulated VSMC migration in vitro, an effect that is inhibited by sIL-6R. However, IL-6 did not modify cell proliferation, collagen type I and contractile protein of VSMC. Our results suggest that exercise induces vascular remodeling. A possible association with IL-6 is proposed. Because sIL-6R inhibits IL-6-induced VSMC migration, a possible mechanism to regulate IL-6-dependent VSMC migration is also proposed.